Comparative and quantitative study of three premier medical institutes in India so as to suggest baseline of key performance indicators for medical colleges - Rajesh Harsvardhan; Akanksha Singh (Wolters Kluwer -Medknow Publications, 2023)
Introduction: There has been substantial increase in the number of medical colleges along with student enrollment necessitate a need for improving the quality of medical education in India. This led to the development of accreditation and ranking system for medical institutions. Key performance indicators (KPIs) for medical institutions can be determined by parameters considered for accreditation and ranking of medical institutes. KPIs for medical institutions are set of quantifiable measurements used to analyze long-term performance and progress of the medical institutions. KPIs provide a focus for strategic and operational improvement, create an analytical basis for decision-making, and help focus attention on parameters that matter most in improving the quality of teaching and learning resources and patient care services provided by the medical institutes. Methodology: A descriptive and quantitative study was conducted to compare secondary data of three premier medical institutions of India, namely, All India Institute of Medical Sciences, New Delhi; Post Graduate Institute of Medical Education and Research, Chandigarh; and Sanjay Gandhi Post Graduate Institute of Medical Sciences, Lucknow. Baseline for KPIs was designed based on the parameters included in external accreditation and ranking, namely, National Accreditation and Assessment Council Accreditation, National Institutional Ranking Framework Ranking, National Accreditation Board for Hospitals and Healthcare Providers Accreditation, and National Accreditation Board for Testing and Calibration Laboratories Accreditation. Observations and Results: Teaching and training identify four KPIs, annual intake of undergraduate students per hospital beds, annul intake of postgraduate students (DM/MCh/MD/MS degree, DNB, Diploma, Certificate programs, Fellowships, PhD) per hospital beds, annual intake of nursing students expressed as ratio of available hospital beds, and annual intake of paramedical and allied students (diploma, degree, pharmacy, etc.) expressed as ratio of available hospital beds. Patient care includes annual outpatient department consultations including casualty (old + new) expressed as ratio of available clinical faculty, annual In-Patient Department (IPD) admission expressed as ratio of available hospital beds, and annual surgeries conducted (operations and procedures) expressed as ratio of available surgeons. Research and publications include total number of extramural projects currently running expressed as ratio of faculty, total amount of extramural grant expressed as ratio of faculty, and total number of indexed research publications per faculty. Conclusion: The KPIs are absolute necessity due to increase in number of medical colleges across the country. KPIs provide a focus for strategic and operational improvement, create an analytical basis for decision-making, and help focus attention on what matters most to enhance the quality and performance of the medical institutes and subsequently uplift the quality of health-care services across the country.